The Effect Of Wovi Liquid Fertilizer And Goat Manure Concentration On Cucumber (Cucumis sativus L) Monas Variety - Diki Pristiono; Syarifa Mayly; Lisdayani Lisdayani (Protech Biosystems Journal, 2025)
Cucumber has the potential to be developed because it has high economic value and promising market opportunities. The main obstacle in increasing cucumber plant production is the physical and chemical conditions of the soil. The addition of nutrients can be done using organic fertilizers. The purpose of the study was to determine the effect of the concentration of wovi liquid fertilizer and goat manure on the yield of Monas variety cucumber plants. This research was conducted in Kotasan Village, Hamlet V-VI B, Galang District, Deli Serdang Regency, with an altitude of 12 meters above sea level. This research was conducted from March to July 2024. This study used a factorial randomized block design consisting of two factors, namely: Factor 1, wovi liquid fertilizer (W) consists of 5 levels, namely: W0 = control, W1 = Dose of liquid fertilizer 5 ml / liter, W2 = Dose of liquid fertilizer 10 ml / liter, W3 = Dose of liquid fertilizer 15 ml / liter, W4 = Dose of liquid fertilizer 20 ml / liter. The second factor of goat manure (O) consists of 2 levels, namely O1 = Dosage of goat manure 10 tons/ha and O2 = Dosage of goat manure 20 tons/ha. The results of the study showed that the use of goat manure and Wovi fertilizer had no significant effect on the number of fruits, fruit length and fruit weight.